THE ROLE OF COMMUNICATION TO THE DIFFERENCES OF FARMER COMMUNITIES IN KEMIREN VILLAGE KECAMATAN GLAGAH BANYUWANGI DISTRICT - Dinna Lestari (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2020)
Agricultural development that have been conducted so far, on the one hand have managed to change the face of agriculture in Indonesia is no exception in the village Kemiren. The origin of the word itself Kemiren according to village elders, village Kemiren ago when first discovered, the village is still forested and there are lots of pecan trees and durian (durian) so that from then on, the area is called "The Village Kemiren". Kemiren village administratively included in Glagah District, Banyuwangi, East Java and historically geneologis-sociological still shows the socio-cultural system of life that has the power of traditional values ​​Osing so that when the leadership of Governor of East Java Basofi Sudirman, Kemiren village set into a tourist village Osing custom. Osing is one of the ethnic community in Banyuwangi and the surrounding area. Osing language and the context of discussion inlah kominkasi interpersonal provide language difference to farmers in the village this Kemiren. The formulation of the problem in this study is the culture of the people of Kemiren Village, Banyuwangi, the second is the role of communication in the language of the farmers of the Kemiren Village community. The research method used in this research is to use a qualitative descriptive approach. The results obtained in this study are how communication plays an important role in the formation of cultural characteristics of the people of Kemiren Village, the majority of whom work as farmers.